SAT0005 RA genetic susceptibility loci are associated with baseline radiographic joint damage in early RA. (23rd January 2014) - Morgan, M.D.; Twigg, S.; Conaghan, P.G.; Hensor, E.M.A.; Worthington, J.; van der Heijde, D.; Emery, P.; Barrett, J.H.; Morgan, A.W.
Abstract : Background: Since 2007 over 30 genetic loci have been associated with susceptibility to rheumatoid arthritis (RA). The functional consequences of many loci are unknown, in particular their role on disease severity. Recently, several studies have investigated these variants in the development and progression of radiographic joint damage in early and established RA [1-4], highlighting their potential as severity markers. Objectives: We aimed to probe the impact of RA susceptibility loci on baseline radiographic joint damage measured using the total modified Sharp/van der Heijde score (TSS) in a RA inception cohort. Methods: Radiographic damage was assessed from plain x-rays of the hands and feet at baseline on 721 patients recruited into the Yorkshire Early Arthritis Register (YEAR) using the modified Sharp/van der Heijde scoring system. Genotyping was performed on 41 single nucleotide polymorphisms (SNP) covering 34 genomic loci associated with RA susceptibility. Matched baseline TSS and genotype data were available on 411 patients with a symptom duration ≤24months. Zero-inflated negative binomial regression was used to model the TSS as count data, estimate incidence rate ratios (IRR) and perform univariate association under a log additive model for each SNP. A p-value threshold for nominal association was set at p<0.05 with a Bonferroni adjusted threshold for 34 loci at p<1.47×10 -3 . Results: The mean symptom duration was 7.4 months (SD 4.2), mean age at onset 58.9 years, 70.8% were female, 13.7% had recorded radiographic damage (TSS>0) and 58.3% were seropositive (ACPA and/or RF). The strongest association mapped to the C8ORF13-BLK locus (rs13277113 p=3.7×10 -5 IRR 2.3 95%CI[1.6-3.4]) and remained significant at 2years (n=313 p=0.016 IRR 1.6 95%CI[1.1-2.3]). Increased TSS was nominally associated with minor alleles at the KIF5A-PIP4K2C and PTPN2 loci (rs1678542 p=0.006 IRR 2.2 95%CI[1.3-4.0] & rs7234029 p=0.03 IRR 1.7 95%CI[1.1-2.7]). Reduced TSS was nominally associated with minor alleles at the TNIP2 and IL2RB loci (rs231707 p=0.03 IRR 0.6 95%CI[0.4-0.9] & rs3218258 p=0.001 IRR 0.5 95%CI[0.4-0.8]). In addition to these findings, we replicated an association with the minor allele of rs26232 in the first intron of c5orf30 (p=0.002 IRR 0.4 95%CI[0.2-0.7]) associated with a lower median Larsen score in a cross-sectional cohort of established RA patients [4]. Conclusions: Investigation of RA susceptibility loci and radiographic joint damage of early RA patients has highlighted several genomic regions of interest as markers of erosive damage at disease onset. The strongest association lies close to a known expression variant in BLK [5], a B-cell specific tyrosine kinase involved in BCR and pre-BCR signaling. Replication in comparable early RA cohorts is now warranted. References: Scherer. H.U., et al., Ann Rheum Dis 2010, 69:567-70 Lie, B.A., et al., Ann Rheum Dis 2007, 66:1604-9 Van der Linden, M.P.M., et al. Arthritis Rheum 2009, 60:2242-7 Kleszcz A., et al., Arthritis Rheum 2010, 62(S10): p1756 Ge, B., et al., Nat Genet 2009, 41:p1216-22 Disclosure of Interest: None Declared